Abandono parental y su influencia en el estado emocional de una estudiante de 13 años de la Unidad Educativa Juan Montalvo del cantón Baba - Landires Guilindro, Landy Belen (2022)
Parental abandonment is a problem that has been present for a long time, however, with the passing of days it is taking on a significant role in the lives of families, affecting infants and adolescents to a greater extent, where various affectations in the emotional, cognitive and social area. In the present research work, the case analysis of a 13-year-old adolescent student of the Juan Montalvo educational unit is proposed, starting from the objective which is to identify how parental abandonment influences the emotional state in the aforementioned adolescent. Initially, the patient comes to the clinic voluntarily, reports feelings of sadness, a feeling of emptiness, hopelessness, lack of interest in her daily activities and automatic thoughts. Regarding the evaluation of their condition, some psychological tests were applied to them; Beck's depression inventory, and the HTP projective test, which allows verifying the emotional state of the patient and knowing features of depression, likewise techniques were used to address the case study such as direct observation, clinical history, interview semi-structured, which allowed to reach a structural diagnosis (F34.1) persistent depressive disorder 300.4 according to the diagnostic criteria of the DSM-V. Finally, the intervention process in the patient was used through a cognitive-behavioral orientation, pointing out in a certain way, it had favorable and satisfactory results in his mental health.